5S Dashboard Design Principles for Self-Service Business Intelligence Tool Users - Lin, Ching-Yi; Liang, Fu-Wen; Li, Sheng-Tun; Lu, Tsung-Hsueh (Journal of Big Data Research, 2018)
Non–information technology (IT) professionals and nonexpert casual users are increasingly adopting self-service business intelligence (SSBI) tools (such as Tableau, Qlik, and Power BI) to create data visualization dashboards. This study identified the most relevant dashboard design principles for SSBI tool users. The research approach included organizing a focus group in which most of the participants were non-IT professionals in health care, extracting recommended principles from the literature, applying these recommended principles by using data on quality of diabetes care to design relevant dashboards, and proposing the following 5S dashboard design principle framework: 1) seeing both the forest and trees, 2) simplicity through self-selection, 3) simplicity through significance, 4) simplicity through synthesis, and 5) storytelling. The third and fourth principles are novel and provide solutions to decision-making problems (such as conflicting results from excessive and discordant indicators) encountered by health care professional in the public sector as well as in other domains. The 5S dashboard design principles are easily memorized and practical and thus enable non-IT professionals and nonexpert casual users to design insightful dashboards efficiently by using SSBI tools.
Keywords: Business intelligence; data visualization dashboard; quality of diabetes care; open data; principle